Mediastinal Hepatocellular Carcinoma with Unknown Primary: An Unusual and Rare Presentation - Koh, P.S.; Yusof, M.M.; Yoong, B.K.; Rajadurai, P. (Humana Press, 2014)
This is an excerpt from the content